Clinical effectiveness and safety of montelukast in asthma. What are the conclusions from clinical trials and meta-analyses? - Hon KLE; Leung TF; Leung AKC (Dove Medical Press, 2014)
Kam Lun Ellis Hon,1 Ting Fan Leung,1 Alexander KC Leung21Department of Paediatrics, The Chinese University of Hong Kong, Prince of Wales Hospital, Shatin, Hong Kong; 2Department of Pediatrics, The University of Calgary, Calgary, AB, CanadaAbstract: Asthma is a common childhood atopic disease associated with chronicity and impaired quality of life. As there is no cure for this disease, treatment relies on avoidance of triggers such as food and aeroallergens, the use of inhaled bronchodilators/corticosteroids and antiallergic or immunomodulating therapies. Inhaled corticosteroids (ICSs) and bronchodilators have been the mainstay. However, in Asia, myths and fallacies regarding Western medicine and corticosteroids are prevalent and lead to nonadherence to treatment. Also, use of traditional and proprietary herbal medicines is popular. In the past decades, a novel class of nonsteroidal immunomodulating montelukasts has become available. This article reviews the evidence for the effectiveness and clinical efficacy of these medications. A number of randomized and controlled trials have been performed over the years. The majority of studies confirm the usefulness of montelukast as monotherapy and add-on therapy to ICS in mild to moderate childhood asthma across all age groups. ICSs are generally superior to montelukasts for asthma management. However, montelukast has a place in the treatment of young children with viral-triggered wheezing diseases, exercise-induced asthma, and in children whose parents are steroid-phobic and find ICS unacceptable.Keywords: cysteinyl leukotriene receptor antagonist, inhaled corticosteroid, randomized control trial, meta analysis